The Hera of Zeus intimate enemy, ultimate spouse - Pirenne-Delforge, Vinciane 1963-; Pironti, Gabriella 1969- (Cambridge University Press, 2022)
The goddess Hera is represented in mythology as an irascible wife and imperfect mother in the face of a frivolous Zeus. Beginning with the Iliad, many narrative traditions depict her wrath, the infidelities of her royal husband and the persecutions to which she subjects his illegitimate offspring. But how to relate this image to the cults of the sovereign goddess in her sanctuaries across Greece? This book uses the Hera of Zeus to open up new perspectives for understanding the society of the gods, the fate of heroes and the lives of men. As the intimate enemy of Zeus but also the fierce guardian of the legitimacy and integrity of the Olympian family, she takes shape in more subtle and complex ways that make it possible to rethink the configuration of power in ancient Greece, with the tensions that inhabited it, and thus how polytheism works
Title from publisher's bibliographic system (viewed on 19 Jan 2022)
Keywords: Hera / (Greek deity); Zeus / (Greek deity); Mythology, Greek